Bilateral Optic Neuritis in a Child Associated Multiple Sclerosis - Permatasari, Dwita; Agustini, Lukisiari; Suhartono, Gatot (Annals of Mechnikov’s Institute, 2020)
Introduction :Optic neuritis can be associated with multiple sclerosis (MS). Therefore, accurate diagnosis, risk assessment and management of patients with optic neuritis associated multiple sclerosis should be assessed. Method :A 5 years old girl suddenly blurred vision in both eyes and headache within 4 days before admitted in outpatient clinic. Patient had no fever and neurologic deficit. Visual acuity in first day were hand movement, color vision difficult to be evaluated in both eyes and right eye positive relative afferent pupillary defect. Posterior segment evaluation showed bilateral edema optic nerve. MRI showed bilateral optic neuritis, chronic plaque in right parietal lobe, right and left centrum semiovale.VEP showed demyelinating lesion in bilateral visual pathway. Patient was given intravenous methylprednisolone 500 mg divided 4 times a day and continued with oral prednisone start on the sixth days. Result :After treatment with intravenous corticosteroid until fifth days follow up, BCVA and color vision improve gradually. At the ninth days follow up, BCVA on right eye (RE) 5/5 and left eye (LE) 5/8.5 pinhole not improve. Ishihara on RE 12/14 and LE 10/14. Ophthalmoscopy examination showed disc edema subsided in the follow up. A month follow up, BCVA and Ishihara on both eye were5/5 and 14/14. Opthalmoscopy examination showed normal optic nerve head. Conclusion :Bilateral optic neuritis in a child associated multiple sclerosis is a challenging case. Intravenous methylprednisolone is the first line drug therapy give better visual outcome. DOI: 10.5281/zenodo.4038934